Vývoj národnostních vztahů v obvodu Obchodní a živnostenské komory v Liberci v 19. století(případová studie) - Jiránek, Tomáš (Univerzita Pardubice, 2001)
Recently, more attention is paid to economic nationalism during the last decades of the Habsburk monarchy. This study deals with the Czech-German relations in the field of economic corporations in the period of Austro-Hungaria Empire, especially the Chambers of Commerce. The dispute was most obvious in the North-East Bohemia, in the region of the Chamber of Commerce of Liberec. Its roots lay in the national and political state of Habsburk monarchy in the last decaded od the 19th century but they were also reflected in the activities of the above mentioned chamber, which lead to the need of establishing a new chamber for the Czechs who lived in the region.
Keywords: národnostní otázky; vztahy; Liberec; 19. století; obchodní a živnostenská komora